Distribution of boophilus microplus and boophilus decoloratus and associated occurrence of babesia species in cattle in the Soutpansberg region, Northern Province, South Africa - Bryson, Nigel Robert (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2002.